2016
DOI: 10.1016/j.colsurfa.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical and geometrical parameters influencing the wettability of smectite clay films

Abstract: International audienceThe wettability of three swelling clays (beidellite, nontronite and montmorillonite) exchanged with different interlayer ions (Li+, Na+, K+ and Ca2+) was investigated by using the static sessile drop method for contact angle measurements. The results show that water contact angles on clay films vary as a function of the nature of the ion with a specific behaviour of K+-exchanged clays. The effect of various parameters influencing contact angle measurements such as relative humidity (RH), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…These findings suggest that HDTBP-Pal can be better dispersed than APTMS-Pal or Purified-Pal. Contac angle measurments have been reported for other clays such as montmorillonite (MMT) [41][42][43], kaolinite [44] and smectite [45]. The values of the surface energy of Pal and modified Pal are on the same order for MMT (68.65 mJ m 22 ) and modified MMT (53.34 mJ m 22 ) with octadecylamine reported in the literature [41].…”
Section: Calculation Of Surface Energymentioning
confidence: 68%
“…These findings suggest that HDTBP-Pal can be better dispersed than APTMS-Pal or Purified-Pal. Contac angle measurments have been reported for other clays such as montmorillonite (MMT) [41][42][43], kaolinite [44] and smectite [45]. The values of the surface energy of Pal and modified Pal are on the same order for MMT (68.65 mJ m 22 ) and modified MMT (53.34 mJ m 22 ) with octadecylamine reported in the literature [41].…”
Section: Calculation Of Surface Energymentioning
confidence: 68%
“…Contact angle measurements have been reported for other mineral clays such as montmorillonite (MMT) [46][47][48], kaolinite [49], and smectite [50] for the purpose of verifying the surface modification of clays. Figure 3 shows profiles of the sessile droplets of ethylene glycol on the surfaces of Pal tablets.…”
Section: Contact Angle Measurementsmentioning
confidence: 99%
“…Even though it has been an extensively researched material for decades, the microscopic understanding of its wetting properties or its exploitation as a membrane is limited. Previous studies on the wetting properties of clays suggest that the wetting properties are linked to its surface charge, the nature of interlayer cations, interlayer water content, and the surface topography [13][14][15] . As far as the effect of exchangeable cations is concerned, a few studies on kaolinite, a non-swelling clay mineral, revealed conflicting results ranging from negligible impact to cation-dependent wettability 13,14,16 .…”
mentioning
confidence: 99%